Quantitative investigation of air gaps entrapped in multilayer thermal protective clothing in low‐level radiation at the moisture condition. (10th October 2014) - Fu, Ming; Weng, Wenguo; Yuan, Hongyong
Summary: The effects of air gaps entrapped within the multilayer protective clothing system on the thermal performance were studied during low‐level radiation (2–10 kW/m 2 ). A bench‐scale apparatus was designed to produce the liquid droplets and simulate human sweat transferring through the multilayer fabric system. Two air gaps located between the outer shell and the moisture barrier (Gap A) and between the moisture barrier and the thermal liner (Gap B) were used with different gap sizes (0, 2, and 5 mm). The thermal resistance analysis for the heat transfer with a multilayer flat wall was used to interpret the effects of air gap. The results show that the total thermal resistance of a multilayer clothing system and the thermal resistances of the two air gaps are linearly related with the level of heat flux. It is also indicated that the air gap position affects the beneficial effect of the gap size. The effect of Gap B to improve the thermal performance is better than that of Gap A. Copyright © 2014 John Wiley & Sons, Ltd.